Proyecto de Consultoría: Soluciones sostenibles de donación para recidar - Altamirano Cobos, Blanca Valentina (2025)
A persistent social problem in Peru is the lack of safe, affordable, and dignified access to clothing and household essentials for low-income families. Many households rely on informal markets where goods are cheaper but often of low quality, sold in unsafe environments, and without guarantees of hygiene or durability. Recidar offers an alternative to these markets by collecting, sorting, and restoring items before reselling them at accessible prices in its Mi Bazar stores. However, a lack of reliable donation streams creates inconsistencies in key product availability. The proposed solution is the scaling of Recidar’s model through partnerships with PUCP and Centrum universities using updated and innovative donation bins as channels for donation collection. The expected social impact is that low-income families in Peru will have increased access to affordable items and would be better able to rely on Mi Bazar stores to have adequate stock. Financially, the donation bins will expand Recidar’s donation streams at a low cost, by leveraging their pre-established donation collection systems and relationships with university partners. Additionally, higher quantities of donations will increase resale volumes and therefore revenues. Environmentally, the donation bin solution uses circular economy practices to support waste reduction in Peru by extending the life of the donated goods. Overall, the donation bin solution positions Recidar to scale its impact sustainably.